The origins of (C ii) emission in local star-forming galaxies - Croxall, Kevin V.; Pellegrini, Eric William (The astrophysical journal, 2017)
The [C ii ] 158 μ m fine-structure line is the brightest emission line observed in local star-forming galaxies. As a major coolant of the gas-phase interstellar medium, [C ii ] balances the heating, including that due to far-ultraviolet photons, which heat the gas via the photoelectric effect. However, the origin of [C ii ] emission remains unclear because C + can be found in multiple phases of the interstellar medium. Here we measure the fractions of [C ii ] emission originating in the ionized and neutral gas phases of a sample of nearby galaxies. We use the [N ii ] 205 μ m fine-structure line to trace the ionized medium, thereby eliminating the strong density dependence that exists in the ratio of [C ii ]/[N ii ] 122 μ m. Using the FIR [C ii ] and [N ii ] emission detected by the KINGFISH (Key Insights on Nearby Galaxies: a Far- Infrared Survey with Herschel ) and Beyond the Peak Herschel programs, we show that 60%-80% of [C ii ] emission originates from neutral gas. We find that the fraction of [C ii ] originating in the neutral medium has a weak dependence on dust temperature and the surface density of star formation, and has a stronger dependence on the gas-phase metallicity. In metal-rich environments, the relatively cooler ionized gas makes substantially larger contributions to total [C ii ] emission than at low abundance, contrary to prior expectations. Approximate calibrations of this metallicity trend are provided.